Criteria, Indicators and Development Levels of Personal and Professional Component of Primary School Teacher's Social Competence in the System of Postgraduate Pedagogical Education: Theoretical Analysis - Оlena Varetska (Vasyl Stefanyk Precarpathian National University, 2017)
The author focuses on the problem of the development of primary school teacher's social competence in the conditions of primary education modernization, proves the necessity of the research and substantiates the criteria, indicators and levels of the specified competency development in the system of postgraduate pedagogical education; illustrates the tools of personal and professional component.